The Cambridge companion to natural law ethics - Angier, Tom P. S. (Cambridge companions, 2019)
Natural law ethics centres on the idea that ethical norms derive from human nature. The field has seen a remarkable revival since the millennium, with new work in Aristotelian metaphysics complementing innovative applied work in bioethics, economics and political theory. Starting with three chapters on the history of natural law ethics, this volume moves on to various twentieth-century theoretical innovations in the tradition, and then to natural law as embedded in the three Abrahamic faiths. It closes with sections on applied natural law ethics and the challenges and prospects for natural law ethics in the twenty-first century. Uniquely interdisciplinary and written without technical jargon, the book will be of great interest to students and researchers in philosophy, theology, political theory and economics. They will find this the go-to resource for cutting-edge thinking in natural law ethics.